Feasibility Studi Business MAC ID ERP for Development of ERP System of Notification of Goods Imports (PIB) Information System for Company Owning Import Identification Number (API) - Setiawan, Wawan; Djatmiko, Budi (Lembaga Riset Mutiara Akbar (LARISMA), 2022)
Today's competitive business environment requires much greater interaction between customers and businesses. The implementation of an Enterprise Resource Planning (ERP) system is one of the strategies that are widely used by companies to improve the quality of their information systems. This is because ERP is part of the company's infrastructure that can support the smooth business processes of companies that implement it. In addition, ERP is also considered as a supporter of business functions, and can increase the company's competitiveness. ERP implementation is a complex step, because of the relationship between one function and another within the company. The information system for the Notification of Import of Goods is very important for companies carrying out import activities due to the efficiency and effectiveness of the customs process for compliance and costs that arise from the implementation of import activities